Penguatan Kemampuan Peserta Didik Dalam Menghadapi Era Society 5.0 Melalui Pembelajaran Matematika - Saputra, Hardika (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Society 5.0 emphasizes the integration of technology into daily life, where humans must maintain control and leverage technology in every aspect. Education plays a crucial role in preparing learners with necessary skills, not just knowledge content but also critical thinking abilities. Mathematics is deemed a vital foundation in facing the Society 5.0 era, aiding in problem-solving and technology utilization. This research aims to explore the role of strengthening mathematical abilities in addressing challenges and opportunities in Society 5.0 era, integrating skill development through mathematics education to prepare adaptive human resources. The study adopts a library research design, gathering data from various sources. It involves activities of reading, noting, and processing research materials from diverse library sources, including online and offline scholarly journals. The conclusion drawn from this research underscores the importance of 21st-century skills, including collaboration, creativity, communication, and critical thinking, for adaptation in the Society 5.0 era. Mathematics education plays a vital role in developing these skills through creative problem-solving, teamwork, idea presentation, and information evaluation, aligning with the demands of the Society 5.0 era.